Characteristics of patients who leave the emergency department without being seen: The first report in China. (8th April 2014) - Liu, Sihuan; Nie, Hu; Huang, Wenxia; Liu, Xiang; Luo, Li; Lau, Wayne Bond; Cao, Yu
Abstract Objective The incidence of patients who leave without being seen (LWBS) by a doctor in the ED in China has not been reported. The purpose of this study is to identify the prevalence and characteristics of the LWBS patient population as well as predictors of LWBS in the ED of a tertiary hospital of China. Methods We conducted a retrospective cohort study of all ED patients from November 2011 to October 2012 in our hospital. Patient age, sex, nationality, time of day, day of week and month of patient presentation, mode of arrival, and triage category were examined as potential predictors of LWBS. Multivariate logistic regression was performed to identify independent predictors of LWBS patients. Results The prevalence of LWBS patients was 10.7%. LWBS patients were nearly equally divided between men and women (52.8% men, 47.2% women). The average age of LWBS patients was significantly younger than non‐LWBS patients (P < 0.001). The majority of LWBS patients (82.2%) arrived on foot, and very few LWBS patients (0.3%) were non‐Chinese. The majority of LWBS patients (94.6%) were assigned to Emergency Severity Index level 3 or 4. Independent predictors of LWBS included paediatric age, lower triage acuity, arrival on foot, time of the day, day of the week and month of presentation. Conclusions Independent LWBS predictors include paediatric patients arriving on foot in the evening with lower acuity problems. Potential risk management strategies should be implemented to decrease or eliminate the LWBS population by improving communication and providing increased comfort measures.